Infestação de plantas daninhas em canaviais: efeito do ambiente de produção e do sistema de colheita, potencial alelopático de cultivares e da benzoxazolinona - Yamauti, Micheli Satomi [UNESP] (2014)
The alterations due presence of sugarcane straw on soil can affect the specific weed composition. The straw can, besides other consequences, promote allelopathic effects on crops and weeds. The aim of this research was to study the straw effect on weed community and test the hydroxamic acids present on sugarcane leaves on weed germination and growth. First essay it were carried out assesments from weed community to obtain specific cover, with 241 data from sugar mil at Ribeirão Preto city zone were used. It was conducted the community organization in pattern cluster using the specific cover percentage, relating with variables from sugarcane environment. In areas with straw presence a minor weed ocurrence was obtained compared to straw ausence, disuniform distribution facilitate the ocurrence of Digitaria spp. Age affected weed community, but species as C. rotundus and morning glory had high infestation in all periods in green sugarcane. The production environment had higher diversity of species on C and D environment. Straw and its distribution, period of harvest and production enviroment had effect on weed community. In a second essay, assesments were carried out in twenty sugarcane plots. In each plot, it was realized a weed evaluation: ocurrence, especific density and aerial dry mass. With the data were calculated the phytosociological indexes. Analyzing all data, despite burned sugarcane presented low number for species diversity, in general, it was not possible to confirm that green sugarcane until second harvest selected weed community when compared to burned cane, or that were different from it. Some essays were carried out to evaluate the possible allelopathy of sugarcane, for the first bioassay were analysed the crude aqueous extracts of green leaves of tem cultivars IAC911099, IACSP955094, IAC873396, CTC2, CTC15, CTC9, RB855156, RB867515, RB855453 and FIJI19. It were evaluated ...